SAVING RESOURCES IN THE OPERATION, MAINTENANCE OF AUTOMOTIVE EQUIPMENT - Khodjaev S.M.; Rakhmonova S.S. (Journals Park Publishing, 2022)
The article discusses the simplest and most effective methods of saving resources in the operation and maintenance of vehicles. Methods for saving fuel consumption, maintenance, spare parts and materials were considered.
Keywords: Automotive equipment; operation, maintenance; fuel consumption